DEVELOPMENT OF MOTOR QUALITY RESISTANCE UNDER ALL ITS FORMS OF MANIFESTATION THROUGH SPECIFIC WAYS OF ATHLETICS IN THE GYMNASSIC CYCLE - Țurcanu Alina Petruța; Vizitiu Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Physical education alongside other fundamental motric activities in the field is an integral part of the measures for harmonious physical development and maintaining an optimal health status for all categories of population. In this study I have studied the extent to which the treatment of the development of the motor quality resistance under all its forms of manifestation through athletic methods has the potential to improve the individual motor ability in the physical education lesson at the level of gymnasium students. I also wanted to implement some resistance development programs in physical education lessons using a number of methodological variants.